Behavior of the T-Shaped Concrete-Filled Steel Tubular Columns after Elevated Temperature - Xianglong Liu; Jicheng Zhang; Hailin Lu; Ning Guan; Jiahao Xiao; Guofeng Du (Advances in Civil Engineering)
The mechanical properties of T-shaped concrete-filled steel tubular (TCFST) short columns under axial compression after elevated temperature are investigated in this paper. A total of 30 TCFST short columns with different temperature (T), steel ratio (α), and duration of heating (t) were tested. The TCFST column was directly fabricated by welding two rectangular steel tubes together. The study mainly investigated the failure modes, the ultimate bearing capacity, the load-displacement, and the load-strain performance of the TCFST short columns. Experimental results indicate that the rectangular steel tubes of the TCFST column have deformation consistency, and the failure mode consists of local crack, drum damage, and shear failure. Additionally, the influence of high temperature on the residual bearing capacity of the TCFST is significant, e.g., a higher temperature can downgrade the ultimate bearing capacity. Finally, a finite element model (FEM) is developed to simulate the performance of the TCFST short columns under elevated temperature, and the results agree with experimental values well. Overall, this investigation can provide some guidance for future studies on damage assessment and reinforcement of the TCFST columns.